1999
DOI: 10.1001/jama.281.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Soliciting the Patient's Agenda

Abstract: Physicians often redirect patients' initial descriptions of their concerns. Once redirected, the descriptions are rarely completed. Consequences of incomplete initial descriptions include late-arising concerns and missed opportunities to gather potentially important patient data. Soliciting the patient's agenda takes little time and can improve interview efficiency and yield increased data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
388
4
28

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 633 publications
(432 citation statements)
references
References 9 publications
12
388
4
28
Order By: Relevance
“…Marvel 3 found that physicians solicited patients' agendas at least once in 75% of encounters, which is close to the 64% found in our study. As suggested in the same study, 3 soliciting the patient agenda decreases the risk of "by-the-way" syndrome.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Marvel 3 found that physicians solicited patients' agendas at least once in 75% of encounters, which is close to the 64% found in our study. As suggested in the same study, 3 soliciting the patient agenda decreases the risk of "by-the-way" syndrome.…”
Section: Discussionsupporting
confidence: 87%
“…As suggested in the same study, 3 soliciting the patient agenda decreases the risk of "by-the-way" syndrome. This is consistent with our results showing that a patient's agenda had to be solicited twice (at the beginning and during the encounter) to decrease the appearance of "by-theway" syndrome.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It has been reported that the typical physician will only listen to a patient for about 18 to 23 seconds before they interrupt the patient and try to explain the patient's problems. 4,5 Wilkins (2006) also posited that listening "aids efficient, accurate diagnosis and healing" and that "blocking listening blunts clinical acumen". 6 In addition, the literature on listening skills in the healthcare setting has focused on the qualified healthcare professionals to the exclusion of the students and trainees in these professions.…”
Section: Introductionmentioning
confidence: 99%